2008
DOI: 10.1016/j.virol.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The linker domain of poly(rC) binding protein 2 is a major determinant in poliovirus cap-independent translation

Abstract: Poliovirus, a member of the enterovirus genus in the family Picornaviridae, is the causative agent of poliomyelitis. Translation of the viral genome is mediated through an internal ribosomal entry site (IRES) encoded within the 5′ noncoding region (5′ NCR). IRES elements are highly structured RNA sequences that facilitate the recruitment of ribosomes for translation. Previous studies have shown that binding of a cellular protein, poly(rC) binding protein 2 (PCBP2), to a major stem-loop structure in the genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 43 publications
(58 reference statements)
1
37
0
Order By: Relevance
“…The unique property of PCBP1 was observed in knockdown studies that point to a housekeeping role for PCBP1 at the quiescent state ( Figure 6). This specificity may serve as another sound piece of evidence for divergent physiological functions of the two proteins as reported elsewhere [40][41][42][43].…”
Section: Discussionsupporting
confidence: 65%
“…The unique property of PCBP1 was observed in knockdown studies that point to a housekeeping role for PCBP1 at the quiescent state ( Figure 6). This specificity may serve as another sound piece of evidence for divergent physiological functions of the two proteins as reported elsewhere [40][41][42][43].…”
Section: Discussionsupporting
confidence: 65%
“…Most of the reports on PCBP2 have focused on its posttranscriptional and translational controls in RNA viruses. For example, PCBP2 has been reported to participate in the replication and translation of many RNA viruses, including poliovirus (15), coxsackievirus (16), and rhinovirus (17). PCBP2 can also bind to the 5′ UTR (18) and 3′ UTR (19) of the HCV gene.…”
Section: Introductionmentioning
confidence: 99%
“…Between domains KH2 and KH3, there is a linker region that has been shown to be an important determinant for binding of PCBP2 to stem-loop IV of poliovirus RNA (25). Previous studies have shown that PCBP2 is cleaved by the viral proteinase 3CD in the linker region between domains KH2 and KH3, removing the third KH domain.…”
mentioning
confidence: 99%
“…Since RNA synthesis occurs in replication complexes, cleaved PCBP2 would be concentrated in these specified complexes, rather than occurring throughout the cell, to allow a switch to RNA replication. PCBP1, an isoform of PCBP, is thought to be generated from a retrotransposition of a fully processed PCBP2 mRNA and differs in the length of the linker region between domains KH2 and KH3 (25,27). Previous work has shown that PCBP1 is able to interact with stem-loop I of the 5= NCR but cannot bind to stem-loop IV (14,25).…”
mentioning
confidence: 99%